Bi3+ assisted enhancement of photoluminescence and thermal sensing of Er3+/Yb3+ co-doped SrGdAlO4 phosphor with unusual stable color. Issue 6 (15th March 2021) - Li, Xiangxiang; Li, Jiangtao; Xu, Xiaofang; Guan, Li; Li, Xuanlin; Zhang, Ruitong; Wang, Fenghe; Wang, Dawei; Zhu, Zizhong; Li, Xu
Abstract: Er 3+ /Yb 3+ co-doped SrGdAlO4 up-conversion phosphors with a tetragonal phase were synthesized using solid state reaction method. The dominant up-conversion luminescent mechanism was deduced through analyzing the power dependencies, energy diagrams and fluorescence lifetimes. It is interesting that the emitting color was almost unchanged when adjusting the dopant contents of Er 3+ and Yb 3+, excitation power and ambient temperature. The emission intensity and color purity of SrGdAlO4 : Er 3+, Yb 3+ sample can be notably enhanced by introducing Bi 3+ ions. X-ray diffraction and band gap analysis illustrated that Bi 3+ ions can increase the asymmetric surrounding environment of the SrGdAlO4 host lattice. Simultaneously, the change of microstrain value showed that the host crystalline is affected by Bi 3+ ions codoping. Optical temperature sensing performance based on the thermal coupled energy levels 2 H11/2 and 4 S3/2 of Er 3+ ions was evaluated in the visible light region. The absolutely sensitivity of SrGdAlO4 : Er 3+, Yb 3+ and SrGdAlO4 : Er 3+, Yb 3+, Bi 3+ are 3.8 × 10 −3  K −1 and 6.1 × 10 −3  K −1 respectively. The results indicated that codoping Bi 3+ ions can improve the luminescent intensity of SrGdAlO4 : Er 3+, Yb 3+, but also strengthen its temperature sensing characteristics.